2014
DOI: 10.1002/2013jd021114
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal cycle of fossil and nonfossil carbon using radiocarbon analyses during CalNex

Abstract: Radiocarbon ( 14 C) analysis is a unique tool to distinguish fossil/nonfossil sources of carbonaceous aerosols. We present 14 C measurements of organic carbon (OC) and total carbon (TC) on highly time resolved filters (3-4 h, typically 12 h or longer have been reported) from 7 days collected during California Research at the Nexus of Air Quality and Climate Change (CalNex) 2010 in Pasadena. Average nonfossil contributions of 58% ± 15% and 51% ± 15% were found for OC and TC, respectively. Results indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
106
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(122 citation statements)
references
References 143 publications
(210 reference statements)
16
106
0
Order By: Relevance
“…The OFR exposed ambient air to varying concentrations of OH radicals in order to obtain photochemical ages much higher than the ambient levels observed at the Pasadena site, and the amount of SOA produced was quantified as a function of OH exposure. Moreover, radiocarbon ( 14 C) analysis has been performed on filter samples and results were combined with positive matrix factorization (PMF) data to determine fossil and nonfossil fractions of the SOA components as reported in Zotter et al (2014). The 14 C results are used for subsequent comparison against the box model from which fossil and non-fossil SOA mass can be estimated.…”
Section: Measurement and Sampling Sitementioning
confidence: 99%
“…The OFR exposed ambient air to varying concentrations of OH radicals in order to obtain photochemical ages much higher than the ambient levels observed at the Pasadena site, and the amount of SOA produced was quantified as a function of OH exposure. Moreover, radiocarbon ( 14 C) analysis has been performed on filter samples and results were combined with positive matrix factorization (PMF) data to determine fossil and nonfossil fractions of the SOA components as reported in Zotter et al (2014). The 14 C results are used for subsequent comparison against the box model from which fossil and non-fossil SOA mass can be estimated.…”
Section: Measurement and Sampling Sitementioning
confidence: 99%
“…It is worthwhile to conduct further study on vehicle-related organic emissions to SVOOA formation. For example, combining radiocarbon and ECOC measurements with the AMS and organic marker measurements, Zotter et al (2014) found that the noon-to-afternoon SVOOA peak can be attributed to the large increase in fossil OC in the measurements in Pasadena, California, US. LVOOA showed a relatively flat diurnal pattern, as was found in Shenzhen (He et al, 2011), in contrast to the significant noon-to-afternoon peaks for LVOOA at rural sites in Kaiping (Huang et al, 2011b) and Heshan (Gong et al, 2012).…”
Section: Sources and Formation Of Oamentioning
confidence: 99%
“…The contemporary end member used for this study was 67.5 , an average of the 2010 biomass burning end member (∆ 14 C = 107.5 ) corresponding to wood smoke and the 2010 biogenic end member (∆ 14 C = 28 ) corresponding to primary and secondary biogenic emissions, meat cooking and combustion of grass, prunings and agricultural waste [42,43]. The fossil fuel end member waś 1000 [44].…”
Section: Filter Measurementsmentioning
confidence: 99%